(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Major depressive disorder (MDD) is increasingly recognized as a systemic pathology of impaired homeostatic neuroplasticity induced by chronic stress. This review synthesizes current evidence demonstrating how hyperactivation of the hypothalamic-pituitary-adrenal (HPA) axis triggers glucocorticoid neurotoxicity and the profound downregulation of Brain-Derived Neurotrophic Factor (BDNF). Structurally, these molecular shifts precipitate an 8–10% volumetric deficit in the hippocampus (Videbech & Ravnkilde, 2004), alongside dendritic retraction and a reduction in synaptic density within the prefrontal cortex (PFC).